Renewable energy : physics, engineering, environmental impacts, economics & planning - Srensen, Bent, 1941- (Academic Press, 2011)
This volume is a true shelf reference, providing a thorough overview of the entire renewable energy sphere, while still functioning as a go-to information source for professionals and students when they need answers about a specific technical issue. Crafted over the last 15 years into a problem-solving tool for engineers, researchers, consultants and planners currently working in the field, as well as a detailed map of the renewables universe for those looking to expand into new technological specialties, Renewable Energy by Sorensen offers the most comprehensive coverage of the subject available. The book has been structured around three parts in order to assist readers in focusing on the issues that impact them the most for a given project or question. PART I covers the basic scientific principles behind all major renewable energy resources, such as solar, wind and biomass. PART II provides in-depth information about how these raw renewable sources can actually be converted into useful forms, transmitted into the grid and stored for future utilization. Finally, PART III undertakes the aspects of energy planning, environmental impacts and socio-economic issues on regional and global levels. In this fourth edition update, new material includes expanded coverage of biofuels, solar conversion, biomass and fuel cells, storage and transmission, and a new chapter on integrated technologies to introduce the hybrid systems now being explored. New surveys and the most recent research findings are included throughout. *New, thoroughly updated fourth edition of the authoritative field guide to the entire Renewable Energy universe *The only books to scientific principles and implementation methods, technologies and socio-economics, environmental impacts and cutting-edge advances, all in one volume. *New material includes expanded coverage of biofuels, solar conversion, biomass and fuel cells, storage and transmission, and a new chapter on integrated systems.